Export problems among small and medium scale industries in klang valley: A preliminary finding / Zahariah Md. Zain, Jamaliah Khalili and Marziah Mokhtar - Md. Zain, Zahariah; Khalili, Jamaliah; Mokhtar, Marziah (Universiti Teknologi MARA Cawangan Pahang, 2008)
This research aims to identify the severity of the export barriers faced by small and medium scales enterprises (SMEs) in Klang Valley.Ten export barrier were listed and the result shows the five main problems are “Adapt Products”,” Fluctuating Exchange Rate”,“Lack of Foreign Channels of Distribution”, “Risks Involved in Selling Abroad”, “Lack of Capital to Finance” and “High Cost of Selling Abroad” regardless of the type of industries. The analysis indicated that the severity of the barriers differs from each industry to another. It is also found that with more years of experience in exporting the weaker will be the barriers since firms are able to cope better and learn from their experiences.